PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN POSITIVE RELATIONSHIP AT WORK TERHADAP TURNOVER INTENTION : TELAAH PADA KARYAWAN HEAD OFFICE PT XYZ - Rahel Veronika (Ultima Management : Jurnal Ilmu Manajemen, 2019)
The aim of this study is to analyze the effect of perceived organizational support and positive relationship at work to turnover intention of head office PT XYZ. As a financing company with good credibility PT XYZ should keep trying to improve the employee's performance by managed turnover intention that occurred in the number 12-15% annually and entered into high category because it has exceeded the turnover rate tolerance limit of 10%. The method used in this research is a descriptive method with non-probability sampling methods with judgmental sampling and snowball sampling techniques. Data is processed through structural equation modeling (SEM) analysis, with the help of Lisrel 8.8 version (n:120). Results of this study showed that there are negative and significant influences from perceived organizational support to turnover intention with t-value of (-3.19), negative and significant influence of the positive relationship at work to the turnover intention with t-value of (-4.16), and the positive and significant influence of the positive relationship at work that partially, which is a partial process of perceived organizational support to the turnover of intention with t-value of ( 2.88). In this research, researchers advise that PT XYZ should ask employees for feedback on what they expect to be repaired when performing the job, so that the work does not become tedious and can reduce turnover rate.